EFEKTIVITAS PERJANJIAN KERJA PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA (P3K) DALAM MENINGKATKAN KUALITAS KERJA DI KANTOR DINAS PERTANIAN DAN KETAHANAN PANGAN KAB. WAJO : (Perspektif Siyasah Syar’iyyah) - Yustika, Yustika; Mustafa, Adriana (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2025)
This study investigates the forms of employment agreements for government employees using the Employment Agreement (P3K) at the Office of Agriculture and Food Security in Wajo Regency, and analyzes effective work standards from the perspective of siyasah syar’iyyah. Performance, involving the actions and inactions of employees, has an impact on their contributions to government institutions. Each employee has specific job criteria, considering work dimensions that identify essential elements of a job. The study aims to comprehend employment agreements within the context of government employees, particularly P3K, at the Office of Agriculture and Food Security in Wajo Regency. It also intends to unveil effective work standards from the standpoint of siyasah syar’iyyah. Although P3K employees are increasingly equated with civil servants (ASN), they remain within a contractual framework with a time limit of 5 years, albeit with the potential for extension through approval from local governments or district chiefs. This research is expected to provide valuable information to the government and society regarding these new regulations. It encourages public enlightenment, motivates the pursuit of respectable employment, and serves as guidance for performing tasks productively and innovatively. Thus, this study can support the enhancement of employee quality and the awareness of the community in a changing government work environment.